PHYSICAL IMPACT OF THEME PARKS EXISTENCE ON SETTLEMENT AREA IN LEMBANG SUBDISTRICT - Arini Shofi Elmia; Wiwik Dwi Pratiwi (Centre For Tourism Planning and Development, 2019)
Theme Park is a type of tourism attraction that able to become the main motivation while tourists visiting a destination. This kind of tourist attraction can bring tourists in large numbers. Farm House and Floating Market are an example of Theme Parks that can gather a large number of tourists which are developed in Lembang Sub-district. Their presence has both positive and negative impacts on the settlement areas where local residents live their livelihoods. This study aims to analyze and assess how the physical impacts occurred by the existence of Theme Parks to settlement areas around. This study uses mixed approach data analysis both qualitative and quantitative. Data analyzed based on both primary and secondary data. The physical impact of the presence of Theme Parks for settlement areas is divided into three aspects: land-use change, changes in housing functions, and the impact on public facilities and infrastructure.